Xylanase Production by Solid-State Fermentation for the Extraction of Xylooligosaccharides from Soybean Hulls - Šekuljica, Nataša; Jakovetić Tanasković, Sonja; Mijalković, Jelena; Simović, Milica; Pavlović, Neda; Đorđević, Nikola; Culetu, Alina; Gazikalović, Ivana; Luković, Nevena; Bakrač, Jelena; Knežević-Jugović, Zorica (Food technology and biotechnology, 2023)
Research background. The development of a novel process for the production of xylooligosaccharides (XOS) based on the 4R concept is made possible by the integration of numerous techniques, especially enzymatic modification together with the physical pretreatment of renewable materials. This study aims to integrate the use of agricultural wastes for the production of xylanase by a new strain of Penicillium sp. and value-added products, XOS. Experimental approach. For the production of xylanase, a solid-state fermentation was performed using wheat bran as substrate. To obtain the most active crude extract of xylanase, the time frame of cultivation was first adjusted. Then, the downstream process for xylanase purification was developed by combining different membrane separation units with size exclusion chromatography. Further characterisation included determination of the optimal pH and temperature, determination of the molecular mass of the purified xylanase and analysis of kinetic parameters. Subsequently, the hydrolytic ability of the partially purified xylanase in the hydrolysis of alkali-extracted hemicellulose from soybean hulls was investigated. Results and conclusions. Our results show that Penicillium rubens produced extracellular xylanase at a yield of 21 U/g during solid-state fermentation. Using two ultrafiltration membranes of 10 and 3 kDa in combination with size exclusion chromatography, a yield of 49 % and 13-fold purification of xylanase was achieved. The purified xylanase (35 kDa) cleaved linear bonds β-(1→4) in beechwood xylan at a maximum rate of 0.64 μmol/(min·mg) and a Michaelis constant of 44 mg/mL. At pH=6 and 45 °C, the purified xylanase showed its maximum activity. The xylanase produced showed a high ability to hydrolyse the hemicellulose fraction isolated from soybean hulls, as confirmed by thin-layer chromatography. In the hydrothermally pretreated hemicellulose hydrolysate, the content of XOS with different degrees of polymerisation was detected, while in the non-pretreated hemicellulose hydrolysate, the content of xylotriose and glucose was confirmed. Novelty and scientific contribution. Future research focusing on the creation of new enzymatic pathways for use in processes to convert renewable materials into value-added products can draw on our findings.